Active surveillance of patients who have sentinel node positive melanoma: An international, multi‐institution evaluation of adoption and early outcomes after the Multicenter Selective Lymphadenectomy Trial II (MSLT‐2). Issue 13 (7th April 2021) - Broman, Kristy Kummerow; Hughes, Tasha; Dossett, Lesly; Sun, James; Kirichenko, Dennis; Carr, Michael J.; Sharma, Avinash; Bartlett, Edmund K.; Nijhuis, Amanda A. G.; Thompson, John F.; Hieken, Tina J.; Kottschade, Lisa; et al.
Abstract : Background: For patients with sentinel lymph node (SLN)‐positive cutaneous melanoma, the Second Multicenter Selective Lymphadenectomy trial demonstrated equivalent disease‐specific survival (DSS) with active surveillance using nodal ultrasound versus completion lymph node dissection (CLND). Adoption and outcomes of active surveillance in clinical practice and in adjuvant therapy recipients are unknown. Methods: In a retrospective cohort of SLN‐positive adults treated at 21 institutions in Australia, Europe, and the United States from June 2017 to November 2019, the authors evaluated the impact of active surveillance and adjuvant therapy on all‐site recurrence‐free survival (RFS), isolated nodal RFS, distant metastasis‐free survival (DMFS), and DSS using Kaplan‐Meier curves and Cox proportional hazard models. Results: Among 6347 SLN biopsies, 1154 (18%) were positive and had initial negative distant staging. In total, 965 patients (84%) received active surveillance, 189 (16%) underwent CLND. Four hundred thirty‐nine patients received adjuvant therapy (surveillance, 38%; CLND, 39%), with the majority (83%) receiving anti–PD‐1 immunotherapy. After a median follow‐up of 11 months, 220 patients developed recurrent disease (surveillance, 19%; CLND, 22%), and 24 died of melanoma (surveillance, 2%; CLND, 4%). Sixty‐eight patients had an isolated nodal recurrence (surveillance, 6%; CLND, 4%). In patients who received adjuvant treatment without undergoing prior CLND, all isolated nodal recurrences were resectable. On risk‐adjusted multivariable analyses, CLND was associated with improved isolated nodal RFS (hazard ratio [HR], 0.36; 95% CI, 0.15‐0.88), but not all‐site RFS (HR, 0.68; 95% CI, 0.45‐1.02). Adjuvant therapy improved all‐site RFS (HR, 0.52; 95% CI, 0.47‐0.57). DSS and DMFS did not differ by nodal management or adjuvant treatment. Conclusions: Active surveillance has been adopted for most SLN‐positive patients. At initial assessment, real‐world outcomes align with randomized trial findings, including in adjuvant therapy recipients. Lay Summary: For patients with melanoma of the skin and microscopic spread to lymph nodes, monitoring with ultrasound is an alternative to surgically removing the remaining lymph nodes. The authors studied adoption and real‐world outcomes of ultrasound monitoring in over 1000 patients treated at 21 centers worldwide, finding that most patients now have ultrasounds instead of surgery. Although slightly more patients have cancer return in the lymph nodes with this strategy, typically, it can be removed with delayed surgery. Compared with up‐front surgery, ultrasound monitoring results in the same overall risk of melanoma coming back at any location or of dying from melanoma. Abstract : In an international cohort of more than 1000 patients with sentinel node‐positive melanoma treated at 21 melanoma centers since the publication of landmark trials supporting active regional nodal basin surveillance using ultrasound as an alternative to completion lymph node dissection, there has been high adoption of active surveillance. Compared with patients who undergo completion lymph node dissection, those who undergo active surveillance have more nodal recurrences but comparable recurrence‐free and disease‐specific survival at this early assessment, including those who receive adjuvant therapy without undergoing prior completion lymph node dissection.